Making journals accessible front & back: examining open journal systems at CSU Northridge. Issue 1 (9th February 2015) - Borchard, Laurie; Biondo, Michael; Kutay, Stephen; Morck, David; Weiss, Andrew Philip
Abstract : Purpose: – This study aims to examine Public Knowledge Project (PKP) Open Journal Systems (OJS) for its overall web accessibility and compliance with the Federal Electronic and Information Technology Accessibility and Compliance Act, also known as Section 508. Design/methodology/approach: – Twenty-one individual web pages in the CSUN test instance of PKP's OJS version 2.4.0 used in three back-end journal development user roles were examined using three web-accessibility tools (WAVE, Fangs, Functional Accessibility Evaluator). Errors in accessibility were then logged and mapped to specific Web Content Accessibility Guidelines (WCAG) criteria. Findings: – In all, 202 accessibility errors were reported across the 21 OJS pages selected for testing. Because of this, the OJS cannot be efficiently utilized by assistive technologies and therefore does not pass the minimal level of acceptability as described in the WCAG 2.0. However, the authors found that the types of errors reported in this study could be simply and effectively remedied. Research limitations/implications: – Further studies will need to corroborate, on a larger scale, the problems of accessibility found in the specific pages. Only three user roles were examined; other roles will need to be analyzed for their own problems with accessibility. Finally, although specific errors were noted, most can be easily fixed. Practical implications: – There is an important need for accessible software design. In the case of CSUN, one of the campus partners will be better served by improving the web accessibility of the authors' online open access journals. Originality/value: – Although many studies and analyses of Section 508 compliance of front-facing web resources have been conducted, very few appear to address the back-end of such tools. This is the first to examine what problems in accessibility journal users with disabilities might encounter as OJS system administrators, journal managers or journal editors.